A General Threshold Signature and Authenticated Encryption Scheme Based on ElGamal System - Yulian Shang; Wuyuan Jia; Lanhua Zhang; Yufei Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Based on ElGamal system, a group-oriented threshold signature and authenticated encryption scheme was put forward. After being signed by a signer group employing threshold signature scheme, the message was transmitted to a particular verifier group, and then the signature was verified through the cooperation of  ones from the verifier group with  members. Similarly, a general authenticated encryption scheme characterized by joint verification was put forward through integrating threshold signature scheme and message recovery technique together; After being encrypted singed by any  ones from a group with  members, the message was transmitted to a particular verifier group with members, and then recovered through the cooperation of any ones from the verifier group. The security of this scheme is based on Shamir threshold scheme and ElGamal system. It realized the directional transmission of message between different groups and enjoyed the characteristics of reduced communication load and lowered calculation complexity, etc. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2828